2007
DOI: 10.1002/jemt.20438
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Distribution of Actin and Tubulin in Human Sperm Nuclear Matrix‐intermediate Filament Whole Mounts—A New Paradigm

Abstract: Sperm is a highly differentiated cell streamlined for fertilization. The function is thus heavily dependent on the cytoskeletal organization. Conventional methods limit the appreciation and correlation of this intricate cytoskeletal filament network in the context of an entire sperm. Our recent successful localization of nonmuscle myosin IIA on sperm nuclear matrix-intermediate filament (NM-IF) preparations from fertile men by embedment-free electron microscopy (EF-EM), prompted us to investigate the antigenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
(34 reference statements)
0
6
0
Order By: Relevance
“…The first studies on immunogold staining applied to human sperm mainly concerned the localization of cytoskeletal proteins at the ultrastructural level [Flaherty et al 1988;Kadam et al 2007). Thereafter, other proteins have been detected such as sperm protein 17, a highly conserved mammalian protein in the testis and spermatozoa, distributed throughout the flagellar fibrous sheath [Chiriva-Internati et al 2009].…”
Section: Tem and Basic Research In Human Spermatozoamentioning
confidence: 99%
“…The first studies on immunogold staining applied to human sperm mainly concerned the localization of cytoskeletal proteins at the ultrastructural level [Flaherty et al 1988;Kadam et al 2007). Thereafter, other proteins have been detected such as sperm protein 17, a highly conserved mammalian protein in the testis and spermatozoa, distributed throughout the flagellar fibrous sheath [Chiriva-Internati et al 2009].…”
Section: Tem and Basic Research In Human Spermatozoamentioning
confidence: 99%
“…In keeping with with these findings, proteomic analyses have revealed that a number of the phosphorylated proteins in human sperm are in fact predominantly or exclusively expressed in the flagella. These include: fibrous sheath AKAPs (AKAP3 and AKAP4) (Carrera et al, 1996;Mandal et al, 1999), CABYR (calcium-binding and tyrosine phosphorylationregulated protein; Naaby-Hansen et al, 2002), tubulin (Kadam et al, 2007), dynein, and chaperones such as heat shock protein (HSP)90 (Ecroyd et al, 2003), HSP40, HSP60 and HSP70 (Mitchell et al, 2007). It is of considerable interest that a number of these proteins (such as HSP90 and tubulin) are known substrates for SRC.…”
Section: Inhibition Of Src Kinase Suppresses Capacitation-associated mentioning
confidence: 99%
“…Previous studies of cytoskeletal reorganization in fixed and living cells after PDT were mostly performed with optical microscopy techniques such as confocal microscopy and immunological staining [7,8]; however, it is difficult to study cytoskeletal structure at the molecular level by optical microscopy because of its limited resolution [9]. A number of studies using electron microscopy to reveal the ultrastructure of the cytoskeleton have also been reported [10,11].…”
Section: Introductionmentioning
confidence: 98%